CHRISTOPHER MARLOWE: A REBELLIOUS SPARK THAT IGNITED THE ELIZABETHAN STAGE - Olimjonova Malika Doniyor qizi ,; Kenjayeva Muxlisa Bahodirovna , (TADQIQOTLAR.UZ, 2024)
Annotation: This article explores the life and works of Christopher Marlowe, a prominent Elizabethan playwright whose innovative approach to drama left an enduring impact on English literature. Despite his short life, Marlowe's plays, characterized by their powerful blank verse, complex characters, and exploration of controversial themes, challenged the conventions of his time and paved the way for the brilliance of William Shakespeare and generations of playwrights to come.